The hotel selection attributes of Middle East tourists in Kuala Lumpur / Fazuin Mohd. Yusoff - Mohd. Yusoff, Fazuin (2010)
It is important that hotel managers and operators must obtain and sustain good hotel attributes in order to enhance guest satisfaction which can lead to profitability. Few studies have been conducted on Middle East tourists’ purchase behaviours and preferences though the highest growth rate of tourist arrivals in Malaysia in 2009 was reported to have come from the Middle East region. The purpose of this study is to identify Middle East tourists’ hotel selection attributes in Kuala Lumpur. Hotel selection dimensions identified from previous research were used to help develop the framework of this descriptive study. The four most important dimensions identified are location, facilities, services and cleanliness. A pilot test was conducted before the questionnaires were distributed to the Middle East tourists staying at the five star hotels within the Kuala Lumpur Golden Triangle area. Data obtained was then analyzed using Statistical Packages for Social Science (SPSS) and descriptive analysis was used to determine the most significant Middle East tourists’ hotel selection attributes in Kuala Lumpur. Findings of this study will help hotel operators to understand Middle East tourists and cater to their needs better. The better served Middle East sector will help increase hotel revenue as well as boost tourist receipts for the country.